My Inspiration Card as a Form of E-Learning in the Cyber Method - Edi Susanto; Mubayinah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Digital-based modernization is increasingly advanced and developing rapidly, impacting on multidimensional patterns of student development. Learning models and media need renewal and innovation to adapt to the times. Research objectives: (1) find out my inspiration card as a form of e-learning in cyber method, (2) find out the implementation of my inspiration card as a form of e-learning in cyber method, (3) find out the implications of my inspiration card as a form of e-learning in cyber method. The results of this study are: (1) My Inspiration Card is an e-learning-based learning media that adapts to the times referring to cognitive, psychomotor and affective intelligence. (2) the application of the Inspiration Card as one of the e-learning-based learning media and its actualization in the application of educational technology is able to follow current educational patterns. (3) there are 6 core achievements as a form of implication of inspiration cards as a form of e-learning, including; love of Allah SWT, responsibility, courage, hard work, fairness and leadership spirit, and tolerance or love of peace.